La démocratie au Japon, singulière et universelle - Delamotte, Guibourg (Gouvernement en question(s), 2022)
Was Japanese democracy born in 1945? Is it the result of a democratic transplant carried out by the Americans? Beyond its particularities, does it meet the universal standards of democracy? This book attempts to answer these questions and to deconstruct preconceived notions about the Japanese political system. It shows, in particular, that democracy took root in Japan from 1947 onwards because the country had some prior experience of political debate and the electoral game. Not only had constitutional monarchy laid the groundwork, but it had also bequeathed to Japan a legacy and political habits which the country long retained. However, the institutional framework of Japanese democracy has been undergoing changes since the 1990s. It is a political system that, despite its imperfections and the crisis of representation it undergoes, displays an ability to question and reform itself.